2020
DOI: 10.1021/acsami.0c06809
|View full text |Cite
|
Sign up to set email alerts
|

Self-polarized Poly(vinylidene fluoride) Ultrathin Film and Its Piezo/Ferroelectric Properties

Abstract: Organic nonvolatile memory with ultralow power consumption is a critical research demand for next-generation memory applications. However, obtaining a large-area, highly oriented ferroelectric ultrathin film with low leakage current and stable ferroelectric switching remains a challenge for achieving low operation voltage in ferroelectric memory transistors. Here, an ideal ferroelectric neat PVDF ultrathin film with a high degree of orientation is fabricated by a melt-draw technique without post-thermal treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…As an example, α crystals of poly­(vinylidene fluoride) can only be applied as normal plastics. However, its β or γ counterparts exhibit excellent piezo- and pyroelectric properties. Therefore, the challenge for regulating the multiscale structure and morphology of semicrystalline polymers has stimulated a great deal of research in multiscale structure regulation of polymers and resulted in the development of advanced technologies for purposeful control of the crystallization process. …”
Section: Introductionmentioning
confidence: 99%
“…As an example, α crystals of poly­(vinylidene fluoride) can only be applied as normal plastics. However, its β or γ counterparts exhibit excellent piezo- and pyroelectric properties. Therefore, the challenge for regulating the multiscale structure and morphology of semicrystalline polymers has stimulated a great deal of research in multiscale structure regulation of polymers and resulted in the development of advanced technologies for purposeful control of the crystallization process. …”
Section: Introductionmentioning
confidence: 99%
“…The coercive voltage is the external voltage where the net polarization of the ferroelectric film is zero, and the coercive voltage is found by measuring the half-width of the hysteresis loop. The lower coercive voltage attributed to the improved crystal quality enables an optimum coupling efficiency between the electric field and net-dipole moment . Hence, the well-defined ferroelectric loop with stable polarization for the phase angle and a typical butterfly loop of the amplitude response directly relates to the enhanced polar nature of the PZA nanocomposite.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This kind of orientation has been referred to as ring-fiber orientation, as schematically presented in Figure 4b, by Kakudo and Kasai [55] and also observed for a PCL/PVC (80/20) blend crystallized at room temperature under a draw ratio of λ = 3.6 at a strain rate of 20 mm/min [51]. For the stretched blends, the vertical c-axis orientation with respect to the strain direction is unusual, since the crystallization of stretched PCL is expected to start from the chains oriented by stretching, similar to the structure of melt-draw induced crystallization of polymers, where the c-axis is always aligned along the stretching direction [11][12][13][14][15][16]. This demonstrates the influence of PVC on the crystal orientation of the PCL.…”
Section: Crystallization Of H-pcl In H-pcl/pvc Blend Under Strainmentioning
confidence: 96%
“…This stimulates the extensive studies of crystallization from oriented (amorphous) chains for different polymeric materials, including individual polymers and polymer blends. The studies on the crystallization from elongated chains of individual polymers demonstrated the formation of a uniaxial (or fiber) orientation of them with the c-axis aligned in the stretching direction, while the aand b-axes were arranged randomly about the c-axis [11][12][13][14][15][16][17][18]. However, the orientation of miscible crystalline/crystalline polymer blends crystallized under strain can be quite different from the uniaxial fiber orientation.…”
Section: Introductionmentioning
confidence: 99%